2011
DOI: 10.3163/1536-5050.99.1.014
|View full text |Cite
|
Sign up to set email alerts
|

Special report: symposium on transformational change in health sciences libraries: space, collections, and roles

Abstract: What is the role of the library in the 21 st century? What roles will computers and books play as libraries reinvent themselves as knowledge management centers? What will these new physical and virtual information hubs look like? What exciting models already exist and what lessons do these teach?A robust renaissance is underway in the world of libraries and, with this special issue of NEWSLINE, we give you a ringside seat. We examine the questions above and many more, culling information from the proceedings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the years ahead, health science libraries will continue to move from a goods‐based economy (books) to a service‐based economy (reference), and to experience‐based economy. (Lynn et al, 2011, p85‐86).…”
Section: Reflectionsmentioning
confidence: 99%
“…In the years ahead, health science libraries will continue to move from a goods‐based economy (books) to a service‐based economy (reference), and to experience‐based economy. (Lynn et al, 2011, p85‐86).…”
Section: Reflectionsmentioning
confidence: 99%
“…Even a 2011 published report coming out of a symposium focusing on the question of the role of the library in the twenty-first century and cosponsored by the National Library of Medicine and AAHSL failed to address skills needed beyond the next decadespecifically those skills such as designing systems to capture tacit knowledge, quality filtering, linking evidence into EHRs, and so on-skills required by the knowledge manager of the future to ensure success [16].…”
Section: The Peer-reviewed Literaturementioning
confidence: 99%
“…In a special report funded by National Library of Medicine, National Institutes of Health, and Department of Health and Human Services, Lynn, FitzSimmons, and Robinson wrote that library users will have less time, more needs, and a desire for information rapidly [3]. Thibodeu also suggested that future roles of librarians should be expanded to include partner, collaborator, advisor, evidence-based medicine expert, educator, and information filter.…”
mentioning
confidence: 99%
“…Thibodeu also suggested that future roles of librarians should be expanded to include partner, collaborator, advisor, evidence-based medicine expert, educator, and information filter. Librarians should be informers of system designs and make libraries more valueable [3].…”
mentioning
confidence: 99%